Application of Challenge Based Learning Model to Students' Critical Thinking Ability in Fiqh Learning - Wahyu Kusuma Mukti; Langputeh, Sukree; Muhamad Fauzi; Achmad Fadil; Irja Putra Pratama; Aristophan Firdaus (PAI RAFAH, 2025)
This study aimed to investigate the application of the Challenge Based Learning (CBL) model in improving students' critical thinking skills in Fiqh learning. The CBL model utilizes environmental challenges as a learning resource. This quantitative study employed tests, observation, and documentation to collect data. Data analysis was conducted using descriptive statistics and the "t" test. The results showed that the CBL model can be effectively applied in Fiqh learning, particularly in zakat material. Students' critical thinking skills improved significantly, with an average score increase from 63.42 to 75.56. Statistical testing revealed that 65.0% of students' thinking abilities were influenced by the CBL model. Additionally, students were more active in participating in learning through the CBL model. The study suggests that the CBL model can be a valuable approach to enhancing critical thinking skills in Fiqh learning. The findings of this study can be used as a reference for educators and researchers to develop effective learning strategies that promote critical thinking skills in students. Furthermore, the study recommends that educators consider incorporating the CBL model into their teaching practices to improve student learning outcomes.